Tiedon geopolitiikka arktisilla alueilla : tapauksena Huippuvuoret - Jauhiainen, Jussi S. (Suomen Maantieteellinen Seura, 2013)
This article researches the geopolitics of knowledge in the context of the Arctic areas. The case regards the world’s northernmost university centre (UNIS) and the global seed vault (GSV) both located in Svalbard. The empirical material is consisted of hundreds of research articles about environment conducted in/about Svalbard (Spitsbergen), strategies and documents of UNIS and GSV, semi-structured questionnaire for the staff of UNIS (51 responses, response rate 67.1%), and observation on site. People, environment and geopolitical interests come together many ways in the production and use of knowledge. Environmental research in Svalbard is mostly conducted according to the rules of modern science and often enhancing technological innovations with applied projects. Some knowledge is open and active, other is closed and passive. Research is also about selective politics of presence in which the researchers in Svalbard and the research topics about Svalbard legitimise the broader national interests regarding the Arctic areas.